(Syginum aromaticum L.) (Isolation of Eugenol and Beta Caryophylene From Clove Leaf Oil) - Tiurlan Farida Hutajulu; Kurnia Hanafiah; Dadang Supriatna (Balai Besar Industri Agro, 2007)
Clove leaf oil is one of the eugenol and beta-caryophylene source essential oils commonly use for chemicals,farmacies,fragrance,and food inductries. The problem of clove leaf oil is poor quality i.e. low eugenol content and dark brown colour,result in price low price.One alternative of increasing its quality and value is by chemical deterpenation method. This method include aging period treatment after reacted with sodium hydroxide for 12 and 24 hour. Eugenol and beta caryophilene content was analised by gas chromatogrphy.The eugenol content extracted from this method was compared with imported eugenol products i.e.containing 85%-99,2% with 70,09%(v/v) yield,aging of 12 hour result in eugenol content 80%-84% and 50.22% (v/v) yield.This method also result in beta caryophylene extrec as side product, aging of 24 hour result in the highest content of beta caryophylene i.e. 80%-85% with 25,22%(v/v)yield,whereas 12 hour aging result in beta caryophylene content of 62%-64% and 24,01% (v/v) yield.